School Principle Leadership in Improving Teacher Professionalism Competency in Schools - Hotmaida Sidabutar; Nathanael Sitanggang; Wildansyah Lubis; Rosnelli Rosnelli (Budapest International Research and Critics University, 2023)
This study aims to analyze: 1) The Leadership Style of the Principal of SMP Santa Lucia Sei Rotan 2) Efforts to Increase the Professionalism of Middle School Teachers of Santa Lucia Sei Rotan, 3) Supporting and Inhibiting Factors of the Principal's Leadership Style in Increasing the Professionalism of SMP Santa Lucia Sei Rotan Teachers. This research uses a descriptive qualitative approach. Research data collection techniques in the form of observation, interviews and documentation. The results of the study reveal three findings, namely: 1) The Principal of SMP Santa Lucia Sei Rotan leads and fosters teachers through democratic means, 2) Efforts to Increase the Professionalism of Teachers of SMP Santa Lucia Sei Rotan, namely through training, direction and coaching of teachers teachers, 3) There are several factors that support and hinder the leadership style of the principal of SMP Santa Lucia Sei Rotan, namely the lack of obedience of teachers in complying with regulations so that it triggers inhibition while the supporting factors that can be used as a reference in improving leadership style are the frequent trainings or seminars held to improve teacher professionalism.